MOMMYWELL: INNOVATIVE INTEGRATED HEALTH APPLICATION FOR IMPROVING MATERNAL AND CHILD HEALTHCARE IN THE DIGITAL ERA - Warman, Sa Bashkaran Adi; Nugroho, Angelita Jasmine; Alini, Julian; Saputro, Tegar Tri; Andreas, Allwin (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The urgent need to address the high maternal and infant mortality rates in Indonesia, emphasizing the imperative to bridge existing gaps in health information and education. It underscores the necessity for comprehensive strategies that encompass broad educational campaigns, accessible resources, and innovative platforms to empower mothers with the knowledge and resources needed to make informed healthcare decisions. The study also acknowledges the transformative potential of mobile applications in advancing maternal and child health, highlighting the challenges of technology accessibility and digital literacy that must be navigated for the widespread and effective utilization of health-related apps. The identified challenges underscore the necessity of ensuring that the benefits offered by mobile applications are accessible to all segments of the population, and efforts to enhance users' ability to navigate and comprehend health-related apps are crucial. In conclusion, the abstract emphasizes the substantial promise of mobile applications in healthcare and the paramount importance of addressing challenges related to technology accessibility and digital literacy through a holistic approach that prioritizes inclusivity, education, and support.